EXPLORING ISLAMIC FINANCE AS A TOOL FOR MITIGATING AGRICULTURAL RISKS - Mahboob , Mohamed Nafeel; Mansor, Fadillah; Madun, Azian (Online Journal of Islamic Management and Finance (OJIMF), 2025)
Agricultural financing plays a critical role in ensuring food security and economic stability in many developing countries. However, farmers face numerous financial risks, including fluctuating commodity prices, climate change, and access to affordable credit. This study aims to revisit Islamic financial principles and systems to explore their potential in addressing the financial risks faced by farmers in Sri Lanka. Islamic finance, with its emphasis on risk-sharing and ethical investment, offers unique opportunities for developing innovative solutions adapted to the agricultural sector. This study has analyzed the applicability of Islamic financial instruments such as Murabaha, Mudarabah, and Salam contracts in agricultural financing in Sri Lanka. By examining the strengths and limitations of these instruments, the research has presented financial resilience and sustainability for farmers. Ultimately, this research aimed to contribute to the broader discourse on sustainable agricultural finance by highlighting the relevance of Islamic finance in mitigating financial risks and fostering inclusive growth in the agricultural sector in Sri Lanka.